U.S. Interests in the Middle East and the Tools for Their Protection - Chahine, Tarek Jarjoura (Arab Journal for Sciences and Research Publishing, 2025)
The study shows that American interests in the Middle East constitute a fundamental pillar of its global strategy, given the geopolitical, economic, and security importance of the region, as The Middle East supplies the United States with approximately 17% of its oil imports, hosts over 30,000 American troops in strategic military bases, and accounts for more than 85 billion in annual trade with the U.S., highlighting its economic, security, and geopolitical significance. The United States has employed a mix of military, diplomatic, and economic tools to safeguard its traditional and emerging interests, which include its allies, oil supplies, countering the expansion of Russian and Chinese influence, confronting Iran and its proxies, ensuring the political stability of allied states, and combating terrorism. However, the rapid regional and international changes necessitate a review and renewal of the tools of American national power in shaping global policy and promoting soft power, in a way that ensures the sustainability of U.S. influence and enhances stability in the region.